FROM THE METAPHOR OF WATER TO CORRESPONDENCES BETWEEN ENESCU, EMINESCU, BLAGA AND THE ROMANIAN SPIRITUALITY - Olguţa LUPU (Studia Universitatis Babeş-Bolyai. Musica)
In the work of George Enescu, nature is regarded not as an intrinsic reality, but rather as an array of elements permanently interacting with the human being, giving birth to a complex connection, sometimes manifested through a harmonious communion, other times garnering dramatic dimensions. Of all the primordial elements, the symbol of water marks Enescu’s entire creation, illustrating the complexity of the relationship between man and nature: from the serene and melancholic pages of his youth, that broach the romantic genre of character miniature (barcarola), to the works characterized by a nostalgic and introspective component with a touch of memoir (in Childhood Impressions or The Villageoise Suite), all the way to the tragedy in Vox Maris – whose similarities with Oedipus require further investigation. Starting from the symbol of water, certain correspondences could be established between Enescu, Eminescu, Blaga and the Romanian spirituality.